DIGITAL LITERACY AND ISLAMIC EDUCATION IN INDONESIA: EXAMINING POLICY, LEARNING PRACTICES, AND TEACHER READINESS - Haris Habibul Fattah; Luqman Hakim; Masdar Hilmy (Program Studi Pendidikan Agama Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2026)
The rapid advancement of digital technology has significantly transformed the educational landscape, including Islamic education. Digital literacy has become an essential competency that extends beyond technical skills to encompass critical thinking, ethical awareness, and responsible engagement with digital information. This study aims to analyze digital literacy policies within Islamic education in Indonesia, examine the implementation of digital literacy-based Islamic Religious Education (PAI) learning practices, and explore teachers’ readiness and competencies in integrating Islamic values with digital literacy in the learning process. This study employed a qualitative approach using a literature review method. Data were collected from relevant scholarly articles, books, and policy documents published between 2020 and 2025 and analyzed through thematic analysis. The findings indicate that the Indonesian government, through the Ministry of Education, Culture, Research, and Technology and the Ministry of Religious Affairs, has implemented various digital transformation policies, including the Merdeka Belajar program, the Merdeka Mengajar Platform, madrasa digitalization initiatives, and the E-Learning Madrasah system to strengthen digital literacy in educational settings. Digital literacy-based PAI learning practices have utilized various digital platforms and media to create more interactive, flexible, and learner-centered learning environments while enhancing students’ critical engagement with religious information in digital spaces. Furthermore, teachers’ readiness plays a crucial role in the successful implementation of digital literacy, as it requires the integration of technological competence, digital pedagogical skills, and the ability to incorporate Islamic values into instructional practices. This study highlights that the successful implementation of digital literacy in Islamic education depends on the synergy between supportive policies, innovative learning practices, and integrated teacher competencies.